2002
DOI: 10.1080/09553000110117359
|View full text |Cite
|
Sign up to set email alerts
|

Chromosomal radiosensitivity in young cancer patients: possible evidence of genetic predisposition

Abstract: The results suggest the possibility that a substantial proportion of early onset cancers are associated with the inheritance of predisposing genes of low penetrance. However, support for this hypothesis requires that the heritability of chromosomal radiosensitivity be demonstrated in family members. In addition, a larger study is now required to investigate the chromosomal radiosensitivity of specific early onset cancers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
26
1
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(31 citation statements)
references
References 16 publications
3
26
1
1
Order By: Relevance
“…Enhanced G 2 chromosomal radiosensitivity has been detected in several welldefined cancer susceptibility syndromes, most notably ataxia telangiectasia [Parshad and Sanford, 2001]. Increased G 2 chromosomal radiosensitivity also has been reported in a high proportion of patients with a diverse range of cancers [Scott et al, 1994a;Parshad et al, 1996;Patel et al, 1997;Scott et al, 1999;Terzoudi et al, 2000;Bondy et al, 2001;Riches et al, 2001;Baeyens et al, 2002;Baria et al, 2002] leading to suggestions that it could be a marker of cancer predisposing genes of low penetrance whose role is to respond to DNA damage Bondy et al, 2001;Baria et al, 2002]. Support for the heritability of chromosomal radiosensitivity across generations can be inferred from family studies Scott, 2000;Curwen et al, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…Enhanced G 2 chromosomal radiosensitivity has been detected in several welldefined cancer susceptibility syndromes, most notably ataxia telangiectasia [Parshad and Sanford, 2001]. Increased G 2 chromosomal radiosensitivity also has been reported in a high proportion of patients with a diverse range of cancers [Scott et al, 1994a;Parshad et al, 1996;Patel et al, 1997;Scott et al, 1999;Terzoudi et al, 2000;Bondy et al, 2001;Riches et al, 2001;Baeyens et al, 2002;Baria et al, 2002] leading to suggestions that it could be a marker of cancer predisposing genes of low penetrance whose role is to respond to DNA damage Bondy et al, 2001;Baria et al, 2002]. Support for the heritability of chromosomal radiosensitivity across generations can be inferred from family studies Scott, 2000;Curwen et al, 2005].…”
Section: Introductionmentioning
confidence: 99%
“…For example, ataxia telangiectasia was originally identified in radiosensitive individuals (reviewed in Lavin and Shiloh, 1999), and recent murine studies demonstrate a predisposition to radiation-induced mammary carcinogenesis in ATM heterozygous mice , strengthening the link between genetic predisposition and radiationinduced genomic instability. Recent studies also suggest that various cancers are associated with predisposition for radiation-induced chromosomal instability Baria et al, 2002). Perhaps the strongest relationship between genetic predisposition and radiation response in human populations is the heterogeneous responses observed in occupationally and accidentally exposed populations (CBEIR, 1990;Chang et al, 1997;Salomaa et al, 1998;Lindholm et al, 1999;An and Kim, 2002;Salomaa et al, 2002;reviewed in Sankaranarayanan, 2001;Sankaranarayanan and Chakraborty, 2001), and in patients who are refractory to medical exposures to ionizing radiation (reviewed in Gudkov and Komarova, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown that enhanced chromosomal radiosensitivity is also present in a significant proportion of cancer patients (Scott et al, 1994(Scott et al, , 1998Parshad et al, 1996;Patel et al, 1997;Terzoudi et al, 2000;Baria et al, 2001Baria et al, , 2002Buchholz and Wu, 2001;Papworth et al, 2001;Riches et al, 2001;Baeyens et al, 2002Baeyens et al, , 2005Ban et al, 2004;Howe et al, 2005;Kolusayin Ozar and Orta, 2005;Mozdarani et al, 2005;Distel et al, 2006;Lisowska et al, 2006;Varga et al, 2006). The majority of data have been collected in studies considering breast cancer patients whose lymphocytes were irradiated in the G 2 phase of the cell cycle (Scott et al, 1994Parshad et al, 1996;Patel et al, 1997;Terzoudi et al, 2000;Baria et al, 2001;Buchholz and Wu, 2001;Riches et al, 2001;Baeyens et al, 2002Baeyens et al, , 2005Howe et al, 2005;Djuzenova et al, 2006;Docherty et al, 2007).…”
mentioning
confidence: 99%